Systemic immune-inflammatory index and systemic inflammation response index in predicting renal impairment in children with type 1 diabetes mellitus - Rehab Elmeazawy; Sarah El Shall; Manal Zaki AbdElsamea; Mohammed Helmi Emara (SpringerOpen, 2024)
Abstract Background The aim of this study was to investigate the role of systemic immune-inflammatory index and systemic inflammation response index in predicting early renal impairment in children with type 1 diabetes mellitus (T1DM). Methods This is a retrospective cohort study which searched the electronic medical records of patients consecutively admitted to Pediatric Endocrinology Unit with the diagnosis of type 1 diabetes mellitus between August 2022 and July 2023. Results A total of 100 children with the diagnosis of T1DM were enrolled in the study. Early stage diabetic nephropathy (DN) was found in 34 patients. Patients with DN showed significantly higher HbA1C, microalbuminuria, cholesterol, TLC, platelet, neutrophil count, NLR, PLR, SII, and SIRI than the DM without DN. It was discovered that DN was independently correlated with NLR, PLR, SII, and SIRI. Conclusions SIRI and SII are easily available and affordable inflammatory markers that may serve as independent early predictors of diabetic nephropathy in individuals with type 1 diabetes.